Letter from J.R. Ackerley to Herbert Read, [March, 1950] - http://id.worldcat.org/fast/12552 (1950)
Part of a collection of letters to Herbert Read from Joe Randolph "J. R." Ackerley (writer and literary editor of the BBC's weekly magazine The Listener).